Efficacy and safety of dupilumab in the treatment of moderate-to-severe atopic dermatitis: a real-life study - Lopes, Mariele Morandin; Castro, Ana Paula Moschione; Ferrisse, Túlio Morandin [UNESP]; Kalil, Jorge; Yang, Ariana Campos; Castro, Fabio Morato (BioExcel, 2025)
Background: Atopic dermatitis (AD) is a chronic inflammatory skin disease that occurs more frequently in children but can also manifest in adults. Approximately 15-20% of children are affected worldwide. Persistent AD may be present in approximately 50% of patients during childhood. Despite the pivotal studies, there are not enough real-life studies using dupilumab, especially in Latin American countries. This study was performed in Brazil and is essential for evaluating this population. The objective of the study was to understand the real-life efficacy and safety of using dupilumab in patients with moderate or severe AD. Methods: Observational, descriptive study based on the biweekly evaluation of 100 patients using the immunobiological dupilumab in an infusion clinic for 16 consecutive weeks. Data collection was conducted from June 2020 to March 2022. To evaluate each sequential SCORing Atopic Dermatitis (SCORAD) value, a repeated measures analysis of variance was performed, with a value of p<0.0001. Results: There was a significant decrease in SCORAD values from the second week of treatment. In 16 weeks, 80% of patients achieved SCORAD-50 and 37% achieved SCORAD-75. Regarding adverse effects, 22% of patients had conjunctivitis, 11% had facial erythema, 1% had herpes simplex and 1% had hypochromia at the application site. Regarding efficacy, the results showed a reduction in SCORAD value by 67.4% in 16 weeks, 72% of patients achieved SCORAD <25, that is, mild atopic dermatitis. Conclusion: This study identified that dupilumab was effective in real life, even outside of the controlled environments of pivotal studies. Additionally, despite conjunctivitis being a common adverse event, no patient required treatment discontinuation.